Effect of antineoplastic drug therapies on carcinoma and aggressive pituitary tumors: a systematic review and meta-analysis - Cardoso, Ana Beatriz Ribeiro [UNESP]; Zimmermann, Amanda Cristina [UNESP]; Raverot, Gerald; Nogueira, Vania dos Santos Nunes [UNESP] (Springer Nature, 2025)
PurposeThis systematic review aims to evaluate tumor control outcomes associated with antineoplastic drug therapies used for aggressive pituitary tumors (APTs) and pituitary carcinomas (PCs).MethodsWe included studies on patients with PC or APT who received one of the following therapies: temozolomide (TMZ), peptide receptor radionuclide therapy (PRRT), everolimus, immune checkpoint inhibitors (ICIs), lapatinib, bevacizumab, capecitabine plus temozolomide (CAPTEM). Search strategies were applied to MEDLINE, EMBASE, LILACS and CENTRAL. Two independent reviewers selected studies, assessed the risk of bias, and extracted data. Proportional meta-analyses were used to calculate overall frequencies of complete response (CR), partial response (PR), stable disease (SD), and progressive disease (PD).ResultsSeventy eight studies were included. TMZ was the most commonly used therapy, followed by ICIs, bevacizumab, PRRT, CAPTEM, lapatinib, and everolimus. Among 434 patients treated with TMZ in studies involving three or more participants, CR occurred in 4% (95% confidence interval [95% CI], 1–13), PR in 33% (95% CI, 28–37), SD in 32% (95% CI, 28–36), and PD in 29% (95% CI, 25–34). For ICIs, PR occurred in 24% (95% CI, 11–44), SD in 12% (95% CI, 4–31), and PD in 67% (95% CI, 24–93).ConclusionTMZ was the most frequently reported therapy, with PR as the predominant outcome. However, the limited data on ICIs, PRRT, bevacizumab, lapatinib, and everolimus yielded imprecise results, highlighting the need for further research with the aim of gaining more insights into treatment effects of antineoplastic drug therapies for APTs and PCs.